Therapeutic combination of radiolabeled CLR1404 with external beam radiation in head and neck cancer model systems. Issue 3 (September 2015) - Morris, Zachary S.; Weichert, Jamey P.; Saker, Jarob; Armstrong, Eric A.; Besemer, Abigail; Bednarz, Bryan; Kimple, Randall J.; Harari, Paul M.
Abstract Background and purpose CLR1404 is a phospholipid ether that exhibits selective uptake and retention in malignant tissues. Radiolabeled CLR1404 enables tumor-specific positron-emission tomography (PET) imaging (124I) and targeted delivery of ionizing radiation (131I). Here we describe the first preclinical studies of this diapeutic molecule in head and neck cancer (HNC) models. Material and methods Tumor-selective distribution of 124I-CLR1404 and therapeutic efficacy of 131I-CLR1404 were tested in HNC cell lines and patient-derived xenograft tumor models. Monte Carlo dose calculations and 124I-CLR1404 PET/CT imaging were used to examine 131I-CLR1404 dosimetry in preclinical HNC tumor models. Results HNC tumor xenograft studies including patient-derived xenografts demonstrate tumor-selective uptake and retention of 124I-CLR1404 resulting in a model of highly conformal dose distribution for 131I-CLR1404. We observe dose-dependent response to 131I-CLR1404 with respect to HNC tumor xenograft growth inhibition and this effect is maintained together with external beam radiation. Conclusions We confirm the utility of CLR1404 for tumor imaging and treatment of HNC. This promising agent warrants further investigation in a developing phase I trial combining 131I-CLR1404 with reduced-dose external beam radiation in patients with loco-regionally recurrent HNC.